Pengaruh Mekanisme Good Corporate Governance (GCG) dan Leverage Terhadap PPH Terutang - Ayatullah Rehullah Khomeny (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2017)
This research aim was to determine the effect of Good Corporate Governance (GCG) Mechanisms and Leverage on the Income Tax Payable with the company size and profitability as control variables. The income tax payable measured by calculating the income tax burden of the company within one tax period. The population were 14 manufacturing companies listed in Indonesia Stock Exchange in 2010-2014 with purposive sampling technique. These results indicated that GCG mechanisms and leverage had significant effect simultaneously on the income tax payable. The partial test results showed that only the external auditor reputation had a positive effect on the income tax payable. Generally, GCG mechanisms embracing the size of commissioner and board directors, the proportion of independent commissioner, managerial ownership, the size of audit committee, and leverage were not affected by the income tax payable.